FAKTOR-FAKTOR KEUANGAN YANG MEMPENGARUHI MARKET SHARE PERBANKAN SYARIAH DI INDONESIA - Bambang Saputra (Department of Accounting-Faculty of Economic and Business (FEB), 2014)
This Study aims to formulate the strategy of market share growth for islamicbangking is need to examine how much the effect of each independent variable is ROA, CAR,FDR, NPF, and REO on the dependent variable (Market Share) on Islamic Banking inIndonesia. The research was conducted on Islamic Banking in Indonesia, BUS and UUS usingfinancial statement data are monthly basis for 36 months, starting in January 2010-December2012. The method of analysis in this study is the analysis Descriptive Statistics and SimpleLinear Regression Analysis. The test results suggest that, first, ROA has a positive significanteffect on Market Share. Second, CAR has a positive significant effect on Market Share. Third,FDR had a positive significant effect on Market Share. Fourth, NPF has a significant negativeeffect on Market Share. Fifth, REO has a significant negative effect on Market Share. Basedthat condition, so, strategy to improve market share growth for Islamic banking must beconcern to qualitative aspects such as sufficient costumer service, product innovative,banking education for costumer, etc. All of that aspects must be supported by government,central bank, Islamic banking, and societyDOI: 10.15408/akt.v7i2.2675